Knowledge, attitude regarding prevention of medication errors among registered nurses - Rohanah Ben; Aini Ahmad; Teh Halimaton Radizuan; Annamma Kunjukunju (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Medication error (ME) is a preventable incident that might lead to patient harm or cause inappropriate medication use while the patient, healthcare professional, or consumer controls the medication. Such incidents might be related to the procedures and systems, including pre-labelling order communication, product labelling, packaging, nomenclature, compounding, dispensing, distribution, administration, education, monitoring, and use, professional practice and health care products. According to World Health Organization (2016), 6-7% of inpatients are exposed to medication errors daily, mostly admitted to the intensive care unit (ICU) and long-term care. Medication errors could result in negative events affecting patient safety, such as adverse events causing disability, injury and even in-hospital death.Purpose: To assess the knowledge regarding the prevention of medication errors and the attitude regarding the prevention of medication errors among registered nurses in a private hospital, particularly in Sarawak.Method: A descriptive quantitative research design cross-sectional survey has been chosen. A set of questionnaires adapted from Di Simone et al. (2018) about knowledge on the administration of IV drugs and attitude, while knowledge on serving medications was adapted from Johari et al. (2013), has been distributed to 122 registered nurses of the private hospital to obtain information about the nurses' knowledge and attitude on the prevention of medication error. The data has been analyzed using the IBM Statistical Package for Science (SPSS) version 20. In this study, a purposive sampling method has been used to enrol eligible participants. Participants’ knowledge and attitude were analyzed using frequency and percentage. The Pearson correlation coefficient test has been used to determine the relationship between knowledge and the socio-demographic data among registered nurses in a private hospital.Results:The study revealed that most of the registered nurses, 93 (76.2%) in one of the private hospitals in Sarawak, East Malaysia, have moderate knowledge of serving medications and a strong correlation between the level of education and knowledge regarding preventing medication error.Conclusion: Nurses have moderate knowledge and positive attitudes in preventing medication errors.